Development of a Neurosurgical Cadaver Laboratory despite Limited Resources - Mayol del Valle, Miguel; De Jesus, Orlando; Vicenty-Padilla, Juan C.; Matos, Alejandro; Inserni, Jaime (Puerto Rico Health Sciences Journal, 2022)
Objective: Our neurosurgical program did not have a cadaver laboratory. The need to create one arose following a decrease in elective cranial cases at our institution after Hurricane Maria. Many neurosurgical programs are in countries where financial support for projects such as developing a cadaver research laboratory cannot be expected from their parent institutions. This article describes how, despite limited resources, a neurosurgical cadaver dissection laboratory can be created and maintained to promote resident education and stimulate future research. Materials and Methods: The University of Puerto Rico Institutional Review Board evaluated and approved the proposal for creating a neurosurgical cadaver laboratory. The process to establish the laboratory was broken into steps. After obtaining the basic materials, the laboratory was created. Results: The creation of our neurosurgical cadaver laboratory was divided into discrete steps that can be undertaken by any institution with a similar goal. First, a suitable workspace was identified. Second, the surgical instruments and equipment required to perform dissections were obtained. Third, cadaveric specimens for dissection and for practicing surgical approaches were acquired. Last, documentation regarding the laboratory’s development was maintained, and an expansion plan was created. We created a dissection laboratory by gathering decommissioned or donated operating room equipment, seeking out contributions from other institutions, and, sometimes, by monetary contribution from the faculty or residents. Conclusion: Clear goals, interdepartmental collaboration, and a high degree of motivation were essential in creating, despite limited resources, a working neurosurgical cadaver laboratory to improve resident education.